The effect of a career choice guidance on self-reported psychological problems - Kunnen, E. S. (Frontiers in Psychology, 2014)
We investigated whether a successful career choice intervention reduces psychological problems, and whether this program was equally effective in participants with low and with high levels of psychological problems. Participants were 45 Dutch students (age 17-24) with career choice problems. They had above average levels of psychological problems before the start of the intervention. These problems decreased significantly following the intervention. With regard to vocational commitment development, the intervention was equally effective for participants with low or average and with (very) high levels of psychological problems before the start of the intervention.